The interplay between leaders’ personality traits and mentoring quality and their impact on mentees’ job satisfaction and job performance - Kumari, Kalpina; Ali, Salima Barkat; Batool, Masooma; Cioca, Lucian-Ionel; Abbas, Jawad (Frontiers in Psychology, 2022)
This study focuses on examining the role of leaders' Five-Factor Model personality traits in their mentoring quality and mentees' job satisfaction. It has also examined how leaders’ mentoring quality impacts mentees' job satisfaction, leading to their job performance at the workplace. The study used an explanatory research methodology to determine the cause-and-effect relationship between mentors' FFM personality characteristics, mentoring quality, and mentees' job satisfaction and job performance. The study was based on path-goal theory and the Big Five-Factor Model of personality characteristics, and a questionnaire was utilized to collect information on the model's constructs. Following the non-probability convenience sampling technique, the empirical data was collected from the academic and non-academic staff of public and private higher education institutions (HEIs) located within Pakistan on five points Likert scale. The proposed hypotheses were tested by using PLS software. Four main conclusions were derived from this study. First, the leaders’ openness to new experiences, agreeableness, and emotional stability substantially influenced the mentees' job satisfaction. Surprisingly, the leaders’ conscientiousness and extraversion qualities did not affect the job satisfaction of the mentees. Second, the findings demonstrated that openness to experience, conscientiousness, and extroversion have a considerable influence on leaders’ mentoring quality, but agreeableness and emotional stability have a negligible impact. Third, the mentoring quality of the leader had a substantial effect on the job satisfaction and work performance of the mentees. Fourth, this study confirmed the belief that mentees' job satisfaction has a favorable influence on their job performance within the context of Pakistan's educational sector. The current study's findings provided valuable insights to the educational institutions about which personality traits they need to foster in their leaders, making them an excellent leader to enhance their mentees’ job satisfaction and job performance within their organizational settings.